Latissimus Dorsi Tendon Reconstruction at the Myotendinous Junction With Acellular Dermal Allograft - Andrew J. Recker BS; LeeAnne Torres MD; Eric Dennis MD; Donald J. Scholten MD, PhD; Brian R. Waterman MD (SAGE Publishing, 2021)
Background: Limited available data have shown latissimus dorsi tendon reconstruction to be an effective treatment for tendon tears in specific subpopulations of elite overhead throwing athletes. Indications: Primary indication for latissimus dorsi tendon reconstruction is a symptomatic, full-thickness humeral avulsion with or without a concomitant teres major tendon tear. Surgical candidates are typically young, high-demand, elite or professional overhead throwing athletes. In this case, the patient is a 29-year-old male former minor league pitcher and current pitching coach with a full-thickness avulsion of the latissimus dorsi tendon. Technique Description: The patient was positioned left lateral decubitus with a dynamic limb positioner maintaining the arm in 90° abduction and maximal internal rotation. This technique used a single posterior axillary incision, which was performed and dissected down to the ruptured latissimus dorsi tendon. We circumferentially applied an acellular dermal allograft to augment the reconstruction at the myotendinous junction. Subsequently, the construct was prepared for transfer with a Krackow suture technique. Suture buttons were used to secure the reconstructed latissimus dorsi tendon to the anatomic footprint on the proximal humerus with a tension slide technique. Results: One case series showed return to the previous level of competition for all baseball pitchers who underwent a latissimus dorsi reconstruction with excellent improvement in visual analog scale pain, American Shoulder and Elbow Surgeons, and Kerlan-Jobe Orthopaedic Clinic scores. Another larger study demonstrated equal return to play rates for professional baseball pitchers with a latissimus dorsi tear treated either nonoperatively or operatively. However, those treated operatively had no decline in performance, whereas the nonoperative cohort saw decline in some statistics. Conclusion: Latissimus dorsi tendon reconstruction using an acellular dermal allograft at the myotendinous junction is a viable treatment option for elite overhead throwing athletes with full-thickness tendon avulsions. It allows for full return to play, particularly if the patient has failed nonoperative management.